Rotor Position Sensorless Control of Wound-Field Flux-Switching Machine Based on High Frequency Square-Wave Voltage Injection - Hong Quan Nguyen (IEEE Access, 2018)
This paper compares three shaft-sensorless control schemes for wound-field flux-switching machines based on a high frequency (HF) square-wave voltage injection technique. An HF model for the machine, with inclusion of the field winding, is first presented. Because the machine had armature and field windings, HF voltage is injected into and processed in the armature winding as with conventional permanent magnet synchronous machines (PMSMs) or injected into one winding and processed in the induced current signal in the other winding. Both the analytical and experimental results reveal that the scheme with d-axis voltage injection and a q-axis induced current process is generally similar to that used for PMSMs. Polarity identification is required to prevent phase errors in the estimated position. The schemes with separate windings for voltage injection and current processing demonstrate superior performance compared with the scheme without, and both schemes do not require polarity identification. Moreover, voltage injection at the field winding has an additional advantage for high-speed operations.